2001
DOI: 10.1152/ajpcell.2001.280.6.c1475
|View full text |Cite
|
Sign up to set email alerts
|

Twisting integrin receptors increases endothelin-1 gene expression in endothelial cells

Abstract: A magnetic twisting stimulator was developed based on the previously published technique of magnetic twisting cytometry. Using ligand-coated ferromagnetic microbeads, this device can apply mechanical stresses with varying amplitudes, duration, frequencies, and waveforms to specific cell surface receptors. Biochemical and biological responses of the cells to the mechanical stimulation can be assayed. Twisting integrin receptors with RGD (Arg-Gly-Asp)-containing peptide-coated beads increased endothelin-1 (ET-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 52 publications
3
91
0
1
Order By: Relevance
“…To transmit the same force, a relatively stiff CSK would require less stretch than a more compliant CSK. Experiments by Chen et al (2001) tentatively support this idea. These investigators found that expression of endothelin-1 increases when integrin receptors in endothelial cells are twisted by attached microbeads, but this response is abolished when drugs are used to block cytoskeletal contraction.…”
Section: Primary Ingredients Of the Hyper-restoration Hypothesismentioning
confidence: 79%
“…To transmit the same force, a relatively stiff CSK would require less stretch than a more compliant CSK. Experiments by Chen et al (2001) tentatively support this idea. These investigators found that expression of endothelin-1 increases when integrin receptors in endothelial cells are twisted by attached microbeads, but this response is abolished when drugs are used to block cytoskeletal contraction.…”
Section: Primary Ingredients Of the Hyper-restoration Hypothesismentioning
confidence: 79%
“…Twisting integrin receptors generates sufficient stress to activate mechanically sensitive genes (13). Models have been created to examine the amplitude and phase of bead rotation and displacement to estimate both solid and viscous characteristics (8,25).…”
Section: Techniques For Mechanically Probing Cellsmentioning
confidence: 99%
“…It is worth noting that the integrin binding partners talin and paxillin that regulate cell adhesion, migration, and integrin conformation (57)(58)(59)(60)(61)(62)(63) could provide a means of mechanotransduction. That signaling has been documented with a magnetic drag force (64) to extend integrin molecules, generating an intracellular calcium response, gene transcription (65) and tyrosine phosphorylation (66 -68).…”
Section: Vla-4 Affinity Modulation By Shearmentioning
confidence: 99%